Agent technology in web based time scheduling / Sharifah Fazlinda Shaik Ismail - Sharifah Fazlinda, Shaik Ismail (2001)
The technology age has, in many ways, makes life easier for human beings. Gone are the days when it takes few days up to few weeks to get letters from one place to another. The emergence of Internet, with its e-business, e-commerce and the like, has left the running of the human life to a click of the mouse with a tool that fits into our palm Similarly, student's enrolment and registration at the university can be done easily and effectively via the Net. The idea of Virtual University, which was once seen as an impossible venture, a foolish dream has finally been materialized. In fact, every day more and more information technology systems and programs have been churned out to facilitate the education field, in particular. This research paper seeks out to come out with a program to help facilitate the Time Table through the Internet. As nowadays the Internet can be access anywhere. People may check the timetable in Web pages. This project will only focusing in FSCIT, UM environment. This document is documentation for the Agent Technology in Web Based Time Scheduling. This paper consists of seven chapters, which covers all the research carried out on this new technology. Chapter 1 is an introduction about the project WXET 3181 Latihan llmiah I. Chapter 2 presents the Literature Review on Agent Technology in Web Based Time Scheduling and the analysis that has been done to identify the usage of this technology to our world. Chapter 3 discusses the Methodology used and the justification for it. It also covers the tools used and also reviews similar software that has been implemented in the Internet. Chapter 4 discusses the System Design and the User Interface. It will elaborate the methods used and demonstrates the related diagram used for the System Model. Chapter 5 presents the Implementation and Testing phase. This chapter will discuss on development of ATWBTS - the web pages, creating images and also the testing phase of the system. Chapter 6 will discuss about the overall evaluation. Problems occurred and how the developer solves the problems. This chapter also will list out the strengths and limitation of the system. And finally, Chapter 7 is the conclusion. Appendixes contain the project time line, references used in developing the system, terminology & acronyms and also the user's guide.